Baseline depression severity as a predictor of single and combination antidepressant treatment outcome: Results from the CO-MED trial - Friedman, Edward S.; Davis, Lori L.; Zisook, Sidney; Wisniewski, Stephen R.; Trivedi, Madhukar H.; Fava, Maurizio; Rush, A. John (European Neuropsychopharmacology, 2012)
The objective of this manuscript is to report associations between baseline depressive severity and (1) baseline sociodemographic and clinical characteristics, (2) treatment outcomes, and (3) differential outcomes for three treatment groups. Six hundred and sixty-five outpatients with nonpsychotic, major depressive disorder were prospectively randomized to treatment with either a selective serotonin reuptake inhibitor (SSRI) monotherapy (escitalopram plus placebo) or one of two antidepressant medication combinations (bupropion-sustained release plus escitalopram, or venlafaxine-extended release plus mirtazapine). For purposes of these analyses, participants were divided into four groups based on baseline severity by the 16-item Quick Inventory of Depressive Symptomatology—Self-Report (QIDS-SR16) total score: mild (0–10) [N = 81], moderate (11–15) [N = 238], severe (16–20) [N = 260] and very severe (21–27) [N = 67]. Treatment outcomes at 12 and 28 weeks were compared among the four severity groups. A history of childhood neglect and/or abuse was strongly associated with the severity of adult depression (1/2 of participants in the very severe group versus 1/5–1/4 of those in the mild group reported abuse and/or neglect). The degree of suicidality (e.g., 15/.4% of the very severe group ever attempted suicide versus none in the mild group), the number of suicide attempts (e.g., mean of .41 ± 1.99 suicide attempts in the severe group versus 0.0 ± 0.0 in the mild group) and severity of suicidality (e.g., 9.2% of participants in very severe group had a plan or made a gesture versus 5.6% in moderate group and none in the mild group) were increased in more severe groups. Participants with a greater baseline depressive severity reported significantly more psychiatric comorbidities (e.g. [at p < .05] increased rates of agoraphobia, bulimia, generalized anxiety, hypocondriasis, panic disorder, post-traumatic stress disorder, social phobia and somatoform disorder, with 23.9% of participants in the very severe group having reported four or more psychiatric disorders versus 1.2% of the mild group). Combination medication treatments were no more effective in treating severe depressions than was SSRI monotherapy. Remission (61.7% of participants in the mild group achieved remission versus 28.4% in the very severe group) is more difficult to achieve in more severe groups than is response (48.8% of participants in the mild group achieved response versus 58.2% in the very severe group) (p < .03). These data may help us to understand the impact of baseline features on antidepressant medication effectiveness and to inform the personalization of depression treatment across the spectrum of depressive severity. (PsycINFO Database Record (c) 2017 APA, all rights reserved)
Keywords: Adolescent; Adult; Aged; Antidepressant Drugs; Antidepressive Agents; Bupropion; Citalopram; Cyclohexanols; Depressive Disorder; Drug Therapy; Drug Therapy, Combination; Female; Humans; Male; Mianserin; Middle Aged; Polypharmacy; Serotonin Reuptake Inhibitors; Serotonin Uptake Inhibitors; Severity (Disorders); Severity of Illness Index; Suicide; Treatment Outcome; Treatment Outcomes; Venlafaxine; Venlafaxine Hydrochloride; antidepressant treatment outcome; depression severity; monotherapy; outpatients; selective serotonin reuptake inhibitor